Understanding medical student evidence-based medicine information seeking in an authentic clinical simulation - Joey Nicholson (Journal of the Medical Library Association, 2020)
Objective: Evidence-based medicine practices of medical students in clinical scenarios are not well understood. Optimal foraging theory (OFT) is one framework that could be useful in breaking apart information-seeking patterns to determine effectiveness and efficiency of different methods of information seeking. The aims of this study were to use OFT to determine the number and type of resources used in information seeking when medical students answer a clinical question, to describe common information-seeking patterns, and identify patterns associated with higher quality answers to a clinical question. Methods: Medical students were observed via screen recordings while they sought evidence related to a clinical question and provided a written response for what they would do for that patient based on the evidence that they found. Results: Half (51%) of study participants used only 1 source before answering the clinical question. While the participants were able to successfully and efficiently navigate point-of-care tools and search engines, searching PubMed was not favored, with only half (48%) of PubMed searches being successful. There were no associations between information-seeking patterns and the quality of answers to the clinical question. Conclusion: Clinically experienced medical students most frequently relied on point-of-care tools alone or in combination with PubMed to answer a clinical question. OFT can be used as a framework to understand the information-seeking practices of medical students in clinical scenarios. This has implications for both teaching and assessment of evidence-based medicine in medical students.